Human Kallikrein 5: An Interesting Novel Biomarker in Ovarian Cancer Patients That Elicits Humoral Response. Issue 6 (1st July 2009) - Bandiera, Elisabetta; Zanotti, Laura; Bignotti, Eliana; Romani, Chiara; Tassi, Renata; Todeschini, Paola; Tognon, Germana; Ragnoli, Monica; Santin, Alessandro Davide; Gion, Massimo; Pecorelli, Sergio; Ravaggi, Antonella
Abstract : Introduction: Kallikrein-related peptidases are secreted serine proteases that exert stimulatory or inhibitory effects on tumor progression. A recent study demonstrated that kallikrein-related peptidase 5 (KLK5) concentration is elevated in serum of patients with ovarian carcinoma. At the moment, the presence of KLK5 in other ovarian pathological lesions is not clearly determined. Moreover, the possibility of a spontaneous humoral immune response to KLK5 has not been studied yet. Methods: In this study, we examined KLK5 levels and antibody (IgG and IgM) response to KLK5 in the serum of 50 healthy women, 50 patients with benign pelvic masses, 17 patients with ovarian borderline tumors, and 50 patients with ovarian carcinomas, using 3 enzyme-linked immunosorbent assay tests available in-house. Results: At 95% specificity on healthy controls, 52% of patients with ovarian carcinoma showed high serum KLK5 (sKLK5) levels, whereas patients with benign pathological lesions or borderline tumors showed almost undetectable sKLK5 levels. Moreover, sKLK5 levels were positively associated to International Federation of Gynaecologists and Obstetricians stage suggesting a possible role of sKLK5 in ovarian cancer progression. Our results about humoral response showed elevated levels of KLK5-specific antibodies in 20% of patients with benign masses, 26% of patients with borderline tumors, and 36% of patients with ovarian carcinomas when compared with healthy controls. Interestingly, KLK5 antibodies were also found in patients with undetectable sKLK5 levels. Conclusions: In conclusion, our results showed that KLK5 is a potential new biomarker to be used in combination with other biomarkers for ovarian cancer detection. Moreover, the existence of KLK5 antibodies suggests that KLK5 might represent a possible target for immune-based therapies.